Association between birth weight and neurodevelopment at age 1–6 months: results from the Wuhan Healthy Baby Cohort - Man Zhang; Bin Zhang; Marufu Martin Gazimbi; Zhong Chen; Yanru Chen; Yizhen Yu; Jie Tang (BMJ Open)
Objective The association between birth weight and infants’ neurodevelopment is not well understood. We aimed to examine the impact of birth weight on neurodevelopment of infants at age 1–6 months using data from the Wuhan Healthy Baby Cohort (WHBC) study.Setting and participants This is a prospective cohort study of 4026 infants from the WHBC study who were born at the Women and Children’s Hospital of Wuhan, China between October 2012 and September 2013 and who had complete healthcare records within 6 months after birth. Participants were categorised into three groups according to their birth weight: low birth weight (LBW; birth weight <2500 g), normal birth weight (2500 g ≤ birth weight <4000 g) and macrosomia (birth weight ≥4000 g).Main outcome measures The main outcomes were development quotient (DQ) and clinical diagnosis of neurodevelopmental delay. Both adjusted regression coefficients and ORs were estimated for LBW and macrosomia.Results Of the 4026 infants, 166 (4.12%) were of LBW and 237 (5.89%) were with macrosomia. Adjusted regression coefficients of LBW and macrosomia for gross motor DQ were −11.18 (95% CI −11.36 to 10.99) and 0.49 (95% CI 0.36 to 0.63), fine motor DQ −6.57 (95% CI −6.76 to −6.39) and −2.73 (95% CI −2.87 to −2.59), adaptability DQ −4.87 (95% CI −5.05 to −4.68) and −1.19 (95% CI −1.33 to −1.05), language DQ −6.23 (95% CI −6.42 to −6.05) and 0.43 (95% CI 0.29 to 0.57), and social behaviour DQ −6.82 (95% CI −7.01 to −6.64) and 1.10 (95% CI 0.96 to 1.24). Adjusted OR of LBW for clinical diagnosis of ‘neurodevelopmental delay’ in gross motor was 2.43 (95% CI 1.65 to 3.60), fine motor 1.49 (95% CI 1.01 to 2.19) and adaptability 1.56 (95% CI 1.06 to 2.31). LBW has no significant effects on ‘neurodevelopmental delay’ in language and social behaviour, and macrosomia has no significant effects on clinical diagnosis of ‘neurodevelopmental delay’ in all domains.Conclusion Both LBW and macrosomia are associated with infants’ DQ, and LBW increases the risk of being diagnosed with ‘neurodevelopmental delay’ in gross motor, fine motor and adaptability among infants aged 1–6 months.